2002
DOI: 10.1086/338625
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Interleukin-12 Deficiency: IL12B Genotype and Clinical Phenotype of 13 Patients from Six Kindreds

Abstract: Interleukin-12 (IL12) is a cytokine that is secreted by activated phagocytes and dendritic cells and that induces interferon-gamma production by natural-killer and T lymphocytes. It consists of two subunits, p35 and p40, which are encoded by IL12A and IL12B, respectively. The first reported patient with a genetic cytokine disorder was a Pakistani child, who was homozygous for a large loss-of-function deletion (g.482+82_856-854del) in IL12B. This IL12-deficient child suffered from infections caused by bacille C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
203
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 264 publications
(212 citation statements)
references
References 49 publications
4
203
0
5
Order By: Relevance
“…These mutations resulted in complete absence of the IL12 p40 subunit. 100,101 In total, mutations in five autosomal genes have been found to cause recurrent disseminated mycobacterial infections. In addition to developing serious infections due to disseminated BCG and atypical mycobacteria, many patients suffer from recurrent systemic infections with non-typhoid species of salmonella.…”
Section: Familial Atypical Mycobacteriosis and Abnormal Ifng Signallingmentioning
confidence: 99%
“…These mutations resulted in complete absence of the IL12 p40 subunit. 100,101 In total, mutations in five autosomal genes have been found to cause recurrent disseminated mycobacterial infections. In addition to developing serious infections due to disseminated BCG and atypical mycobacteria, many patients suffer from recurrent systemic infections with non-typhoid species of salmonella.…”
Section: Familial Atypical Mycobacteriosis and Abnormal Ifng Signallingmentioning
confidence: 99%
“…The clinical manifestations of the disease are heterogenous and range from abdominal abscesses and adenitis to severe sepsis. Several Salmonella serotypes have been identified and include Salmonella Paratyphi 139,140 or non-typhoid Salmonella serotypes such as Salmonella Typhimurium, 140 Salmonella Enteritidis, 139,[141][142][143] Salmonella group B 139,140 or untyped Salmonella. 139,144,145 Host resistance loci identified using QTL analysis…”
Section: Cytokines: Tnf Ifng and Il12mentioning
confidence: 99%
“…Indeed, it has been shown that mutations in the IL-12 p40 gene or the IL-12 receptor lead to reduced IL-12 signaling, which in turn is associated with serious impairment of immunity to intracellular bacteria. 9,10 CD is a chronic granulomatous disease of the intestine that has been shown to be associated with a Th1 T-cellmediated inflammation and high IL-12/IFNg production at histologically affected sites. 8 In addition, studies in animal models of intestinal inflammation have shown that IL-12 is a key cytokine for susceptibility to colitis.…”
Section: Introductionmentioning
confidence: 99%